Sustainability evaluation of a heavy-duty diesel engine used in railways. (1st May 2023) - Tat, Mustafa Ertunc; Hosgor, Oguzhan
Abstract: Heavy-duty diesel engines are essential power units for the Rail and Maritime transportation of people and goods. They are inevitable and consume large amounts of petroleum base fuel, producing substantial emissions. Since they are very bulky and costly to run and maintain, their performance, efficiency, and sustainability data are scarce, also. They are stationary constant-speed engines. Their efficiency values are relatively higher than conventional diesel engines. However, with newer pre and post-injections and fumigation techniques, those engines have significant room for improvement. This study thermodynamically examined a 16-cylinder, 4-stroke, and 90lt heavy-duty diesel engine with 1700 kW rated power output at 1500 rpm. Analyzes were performed on four different same-type engines archive data, obtained by permission, including different speeds and load conditions. Mean energetic and exergetic efficiency values were 12.84% and 11.92% at idling speeds of 650 rpm, 32.00%, and 29.70% at 1000 rpm, 31.35% and 29.10% at 1200 rpm, and 31.35% and 29.09% at the maximum speed of 1500 rpm. The waste-exergy ratio was 71%, the exergy destruction factor 45.5, the environmental effect factor was to be 2.44, and the exergetic sustainability index 0.41. Highlights: This study examines a 16-cylinder and 90 lt heavy-duty railway diesel engine. The engine had a mean effective pressure of 15.39 bar and a rated power generation of 1732 kW at 1500 rpm. Mean energetic, and exergetic efficiency values were 31.35% and 29.09% at the rated power. The waste-exergy ratio was 71%, and the exergy destruction factor was 45.5. The environmental effect factor was to be 2.44, and the exergetic sustainability index was 0.41.